SEDIMENTOLOGY AND GEOCHEMISTRY OF EXTENSIVE VERY COARSE DEEPWATER SUBMARINE FAN SEDIMENTS IN THE MIDDLE JURASSIC OF OMAN, EMPLACED BY GIANT TSUNAMI TRIGGERED BY SUBMARINE MASS FLOWS - Brookfield M.E.; Wilson G.; Blechschmidt I.; Hannigan R.; Coniglio M.; Simonson B. (My University, 2006)
Unusual fining upwards coarse conglomerates overlain by sandstones, thin cherts and green shales occur at the top of the deep-water submarine fan deposits of the Oolitic Limestone Member of the Jurassic Guwayza Formation of Oman. They separate the dominantly submarine fan deposits of the Guwayza Formation from the pelagic shales, fine-grained limestones and cherts of the overlying Sidr Formation. The cross-bedded and graded framework conglomerates occur in extensive, tabular units and are dominated by earlier Mesozoic carbonate clasts with sandy oolitic and peloidal grains derived from fault escarpments and shelf sediments far to the southwest. Subordinate inverse grading, very thick beds, very large floating clasts (up to 100 m long in places) indicate deposition from catastrophic debris flows. Though most palaeocurrents indicate flow from off the platform to the southwest, hummocky cross-bedding shows divergent palaeocurrents suggesting movement in part by deep-water waves. The beds are too coarse for antidune formation and the conglomerate to sand hummocks indicate decelerating flow. There are no nearby large objects to deflect turbidity currents to form divergent flows. We consider that the hummocky cross-stratification, like that in shallow water, was formed by interfering waves. That such coarse, tabular conglomerates affected by wave action occur over extensive areas across deep submarine fan environments, suggests deposition by high-velocity seaward-moving debris and grain flows followed by reworking by waves large enough to redistribute coarse sediment in deep water. The only waves large enough are those of giant tsunami. Petrology and geochemistry show no impact or explosive volcanic constituents in the finer units and the waves involved are too large for generation directly by submarine fault displacements. We suggest that the top Guwayza conglomerates were deposited by very large submarine slides which were then reworked by the tsunami generated by them. Such contemporary massive slope failure deposits are present on the adjacent slope and shelf margin. © 2006 Elsevier B.V. All rights reserved.
Keywords: DEPOSITS; JURASSIC; OMAN; TSUNAMI; Mesozoic::Jurassic; Мезозой::Юрская